2020
DOI: 10.5005/jp-journals-10071-23645
|View full text |Cite
|
Sign up to set email alerts
|

Hospitals may Become “Disease Hotspots” for COVID-19 amid Shortage of Personal Protective Equipment

Abstract: How to cite this article: Patel MP, Kute VB, Goswami J, Balwani MR. Hospitals may Become “Disease Hotspots” for COVID-19 amid Shortage of Personal Protective Equipment. Indian J Crit Care Med 2020;24(11):1145–1146.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[18]. A number of related reviews were reported by Patel et al [17], Singh et al [18], Singh et al [19] and Arora et al [20].…”
Section: What Other Steps Should a Healthmentioning
confidence: 96%
“…[18]. A number of related reviews were reported by Patel et al [17], Singh et al [18], Singh et al [19] and Arora et al [20].…”
Section: What Other Steps Should a Healthmentioning
confidence: 96%
“…Antiinflammatory, anti-oxidants medicines or tablets such supplements of Vitamin C, Vitamin D, probiotic can be advised to take as a prophylactics in order to ward off the disease but strictly under medical supervision. Balance diet and adequate exercise is also able to act as potential prophylactics in if followed properly [13][14][15][16][17][18][19][20][21][22].…”
Section: Prophylactics For Covid-19mentioning
confidence: 99%
“… 3 Indeed, HCW have been disproportionately affected by acquiring infection in their line of work. 4 , 5 The importance of a good seal between the face and the N95 respirator in preventing the transmission of infection to the HCW cannot be emphasized enough.…”
Section: Introductionmentioning
confidence: 99%